Screening of lipophilic marine toxins in marine aquaculture environment using liquid chromatography–mass spectrometry. (February 2017) - Chen, Junhui; Li, Xin; Wang, Shuai; Chen, Farong; Cao, Wei; Sun, Chengjun; Zheng, Li; Wang, Xiaoru
Abstract: This study aimed to develop an exact mass suspect screening approach to perform finding of multiple lipophilic marine toxins (LMTs) in seawater, suspended particulate matter (SPM), and marine sediment from marine aquaculture area using liquid chromatography-time of flight mass spectrometry (LC-TOF/MS). The method was validated and proven to be reliable for the screening of various LMTs. Then, the method was applied to screen LMTs in marine environmental samples collected from mariculture area of Jiaozhou Bay, China. Okadaic acid (OA), pectenotoxin 2 (PTX2), etc were detected and tentatively identified. Positive detection results were confirmed by liquid chromatography-tandem mass spectrometry (LC–MS/MS), and contents of OA and PTX2 in seawater, SPM and marine sediment were also quantified. The mean concentration of OA ranged from 2.71 to 14.06 ng L −1 in seawater and from 0.78 to 3.34 ng g −1 dry weight in marine sediment. The mean concentration of PTX2 ranged from 0.86 to 7.90 ng L −1 in seawater, from 1.56 to 10.67 ng in SPM obtained from 1 L seawater sample and from 0.95 to 2.23 ng g −1 dry weight in marine sediment. The above results suggested that the proposed method was convenient and reliable for the screening of LMTs in different marine environmental samples. In addition, typical LMTs exist in different marine environmental media of the mariculture area of Jiaozhou Bay, China. Follow-up studies should focus on improving current understanding on the environmental behavior of these LMTs in the marine aquaculture environment. Highlights: Development of a LC-TOF/MS method for screening of different classes of lipophilic marine toxins. Analysis of lipophilic marine toxins in different environmental samples of Jiaozhou Bay was achieved. Two types of lipophilic marine toxins were found in the analyzed samples from mariculture environment. Environmental risks of the mariculture area posed by lipophilic marine toxins need more attention.